Answer:
11
Step-by-step explanation:
2x + 3
2(4) + 3 .......................replace x with 4
8 + 3
11
Answer:
v(0) = 32,000 . . . dollars
v(13) = 16,427 . . . dollars
Step-by-step explanation:
The initial value is the value of the function for t=0. Put that into the formula and evaluate.
v(0) = 32,000(0.95^0) = 32,000 . . . . dollars
__
The value after 13 years is the function value for t=13. Put that into the formula and evaluate.
v(13) = 32,000(0.95^13) ≈ 32,000·0.513342 ≈ 16,427 . . . . dollars
Answer:
C
Step-by-step explanation:
A closed circle means inclusive, and -2 is included in values that would make the equation true. Then you just have to test another number greater than and less than -2 to see which way the arrow should point.
-3(-3) + 1 < 7
9 + 1 < 7
10 < 7 FALSE
-3(0) + 1 < 7
1 < 7 TRUE
All values (including -2) will make this equation true
Answer:
y= -3/2x+9
Step-by-step explanation:
Well we have to know that to find a line perpendicular to a given line, you have to have opposite slopes. So that makes the equation begin as y=-3/2x because it's opposite of y=2/3x. Then we have to make sure it goes through the point (4,3). To do that, I tweaked the numbers in my graphing calculator and it worked with 9! So the equation is y= -3/2x+9
(A) Product of
and
is:
![(-2x^{3}+x-5)(x^{3}-3x-4)](https://tex.z-dn.net/?f=%28-2x%5E%7B3%7D%2Bx-5%29%28x%5E%7B3%7D-3x-4%29)
![=-2x^{3}(x^{3}-3x-4)+x(x^{3}-3x-4)-5(x^{3}-3x-4)](https://tex.z-dn.net/?f=%3D-2x%5E%7B3%7D%28x%5E%7B3%7D-3x-4%29%2Bx%28x%5E%7B3%7D-3x-4%29-5%28x%5E%7B3%7D-3x-4%29)
![=(-2x^{3})(x^{3})+(-2x^{3})(-3x)+(-2x^{3})(-4)+x(x^{3})+(x)(-3x)+(x)(-4)+(-5)(x^{3})+(-5)(-3x)+(-5)(-4)](https://tex.z-dn.net/?f=%3D%28-2x%5E%7B3%7D%29%28x%5E%7B3%7D%29%2B%28-2x%5E%7B3%7D%29%28-3x%29%2B%28-2x%5E%7B3%7D%29%28-4%29%2Bx%28x%5E%7B3%7D%29%2B%28x%29%28-3x%29%2B%28x%29%28-4%29%2B%28-5%29%28x%5E%7B3%7D%29%2B%28-5%29%28-3x%29%2B%28-5%29%28-4%29)
![=-2x^{6}+6x^{4}+8x^{3}+x^{4}-3x^{2}-4x-5x^{3}+15x+20](https://tex.z-dn.net/?f=%3D-2x%5E%7B6%7D%2B6x%5E%7B4%7D%2B8x%5E%7B3%7D%2Bx%5E%7B4%7D-3x%5E%7B2%7D-4x-5x%5E%7B3%7D%2B15x%2B20)
![=-2x^{6}+6x^{4}+x^{4}+ 8x^{3}-5x^{3}-3x^{2}-4x+15x+20](https://tex.z-dn.net/?f=%3D-2x%5E%7B6%7D%2B6x%5E%7B4%7D%2Bx%5E%7B4%7D%2B%208x%5E%7B3%7D-5x%5E%7B3%7D-3x%5E%7B2%7D-4x%2B15x%2B20)
![=-2x^{6}+7x^{4}+3x^{3}-3x^{2}+11x+20](https://tex.z-dn.net/?f=%3D-2x%5E%7B6%7D%2B7x%5E%7B4%7D%2B3x%5E%7B3%7D-3x%5E%7B2%7D%2B11x%2B20)
(B) Yes.
Product of
and
= Product of
and
because multiplication is commutative.
Commutative Property of multiplication says that a.b = b.a.
Thus, multiplication is same irrespective of the order of two numbers.